A Case for Procedural Justice Climate: Development and Test of a Multilevel Model - Naumann, Stefanie E.; Bennett, Nathan (Academy of Management Journal, 2000)
Current conceptualizations of procedural justice focus largely on the individual level of analysis; no framework exists for examining procedural justice's social context. Empirical tests reported here offer some support for group-level and cross-level hypotheses. Work group perceptions of cohesion and supervisor visibility in demonstrating procedural justice were associated with the development of procedural justice climate. Procedural justice climate was positively associated with helping behaviors after the effects of individual procedural justice perceptions were controlled for.